PENDEKATAN RULE OF REASON DALAM PRAKTEK JUAL RUGI YANG MENGAKIBATKAN KERUGIAN PELAKU USAHA PESAING (Studi Kasus Putusan KPPU Nomor 03/KPPU-L/2020) - Putriani Rizki Anggraeni (2022)
This study aims to analyze the use of the rule of reason approach by KPPU in resolving predatory pricing cases, the practice of predatory pricing has a negative impact on market competition. unfair business competition through Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition (hereinafter referred to as Law No. 5/1999). The use of the rule of reason requires further proof, in which an action by a business actor will be analyzed regarding the negative impact of such action on the business competition climate. This further proof becomes the complexity of the application of the rule of reason approach. On the other hand, there is only one case related to predatory pricing which was found guilty by KPPU, namely decision number 03/KPPU-L/2020. The method applied in this research is a normative legal research method which is carried out by examining library materials or secondary data with a statutory approach (statue approach) and a case approach (case approach). The results of the study show that predatory prices from the results of predatory pricing can result in significant and widespread effects, both for competing business actors and consumers, and there are several tests that can be carried out by KPPU to make a decision on predatory pricing case. The conclusion of this study is that the application of the rule of reason carried out by KPPU in imposing a decision number 03/KPPU-L/2020 against PT Conch South Kalimantan Cement is carried out by means of a recoupment test (test whether or not there is an attempt to cover losses experienced when selling at a loss). and Price-Cost Test (test comparison of selling prices and production costs). Keywords: Predatory Pricing, Rule of Reason, Competition Law